2011
DOI: 10.3109/01676830.2011.580035
|View full text |Cite
|
Sign up to set email alerts
|

Custom Ocular Prosthesis in Children: How Often is a Change Required?

Abstract: A change of prosthesis is required between 18-26 months following prosthesis placement in children. Over an average of 18 months, a change in the prosthesis was required in 41%, with the youngest age group having the highest exchange rate (47%), and the oldest group the lowest (29%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…12 With increasing age, the ocular prosthesis certainly requires replacement or modification. According to the results of a survey by Raizada et al, 13 change of prosthesis or altering existing prosthesis in growing children was required in 41% children between 18 and 26 months after the prosthesis was delivered.…”
Section: Discussionmentioning
confidence: 99%
“…12 With increasing age, the ocular prosthesis certainly requires replacement or modification. According to the results of a survey by Raizada et al, 13 change of prosthesis or altering existing prosthesis in growing children was required in 41% children between 18 and 26 months after the prosthesis was delivered.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in how often children require new artificial eyes were highlighted in this study, ranging from 1to 4 years with 2 years being the average. Rather than provide a time-span to the change of an artificial eye, Raizada et al [23] and Shaikh et al [24] reported that a change is indicated when the prosthesis rotates within the socket, lose fit, decentration of the cornea and discolouration of the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of prosthesis has been proven to play a definite role in stimulating the orbital growth. In the early childhood, orbital volume increases in a linear fashion78 and a change of prosthesis is required between 18 months and 26 months following prosthesis placement in children 9. The regular replacement or modification of prosthesis is important to give continuous stimulus for socket growth 10…”
Section: Discussionmentioning
confidence: 99%